Prosedur Percutaneous Trans Luminal Angioplasty (PTA) Pada Pasien Dengan Kasus Aneurisma Artery Popliteal (AAP) - Muh Reza Mappagau; Putu Adi Susanta (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Popliteal Artery Aneurysm (AAP) is a pathological dilation of the popliteal artery, and although often asymptomatic, can lead to serious complications such as rupture, thrombosis, or embolism. Aneurysms if ruptured can result in internal bleeding such as, stroke, and can sometimes be fatal. This research method is a literature review study, where literature exploration is carried out in various databases with keywords such as Percutaneous Transluminal Angioplasty (PTA)